BEHAVIORISM IN AYU UTAMI’S NOVEL SAMAN - Yuni Akrama; M. Manugeren; Irma Khoirat (Universitas Islam Sumatera Utara, 2023)
Behavior is a series of causes and effects of the stimulus and response. The response occurs as a result of the given stimulus. In this regard, this study aims to dissect changes in the behavior of the major characters through stimulus and responses that occur in Ayu Utami's novel Saman. This research is a qualitative descriptive study with a literary psychology approach supported by Skinner's theory of behaviorism. According to Skinner, the relationship between stimulus and response occurs through interaction with the environment, which then causes changes in behavior. The data collection technique used in this research is library study. The data analysis technique in this research is descriptive qualitative which begins with data analysis, description of the classification results, and conclusions. The results show that the major characters in this novel experience behavioral changes through the perspective of stimulus and response related to two points of discussion: parental advice and love. In one case heeding parental advice brings good to others and in another disaster; so is love, one runs with risk and the other goes smoothly.